HIERARCHY OF HUMAN NEEDS ON RACHEL WARD'S NUMBER - Rudyanto Rudyanto; Apsari Fajar Prifantini; Siti Nur Hidayah (EL2J (English Language and Literature Journal), 2022)
This study analyses novel entitled of the novel is “Number” by Rachel Ward. Therefore, the writer is interested to conducting research to know human needs in Rachel Wards Number. By using a psychological approach to analyse psychological problems in Rachel Ward''s novel entitled Number .It is a novel that tells how the psychological aspect of Jem when he knows when someone will die and is related to his love relationship with Spyder who was the accused in the London Eyes bombing, but not Spyder. In this study, the researcher completed the data using a descriptive analysis approach. This qualitative descriptive method was used to analyze and interpret the data, and the information was gathered in the form of words, text, and explanations instead of a number. This approach aims to explain how is human needs Rachel Ward‟s novel “Numbers”In this study, the writer presents data analysis based on five types of Human Needs in Rachel Ward''s novel "Numbers". According to Abraham Maslow''s Hierarchy of Needs, there are five types human needs that is Self Actualization, Esteem, Love/Belonging, Safety, and Physiological. To understand the data collection, Hierarchy of Needs among relationship between Spyder and Jem in the novel most exposed is self actualization which is how big love Jem to Spider and also how love’s Jem to Spyder, the second esteem which is Spyder and Jem try to not hurt their heart each other. They care and respect between them, The third is love/belonging that show they own each other, and The fourth is Safety which expresses for they care for each other. And fifth is physiological that show how they emotion to face their faith.